PENGARUH MOTIVASI, KOMPENSASI FINANSIAL DAN LINGKUNGAN KERJA FISIK TERHADAP PRODUKTIVITAS KARYAWAN PADA PT. ARTHA PRIMA FINANCE DENPASAR - Sudiarta, I Gede Arya; Indrawati, Ayu Desi (E-Jurnal Manajemen; Vol 4 No 2 (2015), 2015)
The purpose of this study was to determine the influence of motivation, financial compensation and the physical work environment on employee productivity at PT. Artha Prima Finance Denpasar. This study used a qualitative research using surveys and questionnaires to 54 employees of PT. Artha Prima Finance Denpasar. The analysis technique used in this study is the multiple linear regression analysis. Obtained findings that work motivation variables significantly positive effect on the productivity of employees. Furthermore, the variable compensation financially significant positive effect on the productivity of employees. Finally, the physical work environment variables significantly positive effect on the productivity of employees.
Keywords: Motivasi Kerja; Kompensasi Finansial; Lingkungan Kerja Fisik; Produktivitas Karyawan